2013
DOI: 10.1016/j.bandl.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potential evidence for animacy processing asymmetries during sentence comprehension

Abstract: a b s t r a c tThe animacy distinction is deeply rooted in the language faculty. A key example is differential object marking, the phenomenon where animate sentential objects receive specific marking. We used eventrelated potentials to examine the neural processing consequences of case-marking violations on animate and inanimate direct objects in Spanish. Inanimate objects with incorrect prepositional case marker 'a' ('al suelo') elicited a P600 effect compared to unmarked objects, consistent with previous lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Although syntactic deficits are more often associated with the AN component, later-occurring negativities resembling the N400 component have been found for morphosyntactic violations (e.g., [48, 69]). As such, recent work has suggested that the dominance of the N400 or the P600 component provides insight into the competition between two interactive processing “streams” [29, 52, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Although syntactic deficits are more often associated with the AN component, later-occurring negativities resembling the N400 component have been found for morphosyntactic violations (e.g., [48, 69]). As such, recent work has suggested that the dominance of the N400 or the P600 component provides insight into the competition between two interactive processing “streams” [29, 52, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Nieuwland et al (2013) found that ungrammatical superfluous case marking on inanimate direct objects gave rise to a P600 effect compared to a grammatical condition, which is commonly observed with syntactic violations, but that ungrammatical missing markers on animate direct objects led to an N400 effect as compared to grammatical marking, which is commonly taken as an indicator of semantic difficulty in sentence comprehension. This outcome thus demonstrates the multifaceted nature of DOM in L1 Spanish and demonstrates the importance of semantic principles with animate objects in particular.…”
Section: Case Marking In Spanishmentioning
confidence: 96%
“…Most ERP research on animacy processing has used the N400 (Kutas & Hillyard, 1980), an ERP component strongly associated with semantic retrieval and integration processes (Kutas & Federmeier, 2011;Van Berkum, 2009). For example, words that meet the animacy requirements or preferences imposed by the preceding context elicit smaller N400 amplitudes than words that do not, suggesting a processing advantage for words that meet animacy restrictions or preferences (e.g., Nieuwland, Martin, & Carreiras, 2013;Nieuwland & Van Berkum, 2005Paczynski & Kuperberg, 2012). Sentence-initial animate nouns elicit smaller N400s than appropriately matched inanimate nouns (Weckerly & Kutas, 1999), a finding that is consistent with the tendency of English speakers to start sentences with animate entities (e.g., Branigan, Pickering, & Tanaka, 2008; see also Clark, 1965), and which therefore leads to a preference for sentence-initial animate nouns in listeners and readers.…”
Section: Effects Of Animacymentioning
confidence: 99%